Drag of generic round-shaped bodies in supersonic flow - Yeo, Dawson Dasheng. (2012)
In the field of long ranged military ballistics, the accurate prediction of drag forces acting on the projectile allows for a higher degree of precision on the desired target. In war, this could be the factor that decides an accurate hit on the enemy or an accidental bombardment of ally forces. This report is focused on the prediction of drag forces on the reference object, a M549 155mm projectile used by the United States Field Artillery. The flight conditions of the projectile were varied from sea level conditions to dynamic pressures in the range of 1000 to 2500 psf. The flying Mach number was varied from Mach number 1.5 to Mach number 4. Next, the geometry of the reference object was varied from a half conical angle of 5° to 30° in an attempt to investigate the effects of such changes on the drag characteristics. For each geometrical variation, the flying conditions were also varied in the same way described above. Analytical calculations based on potential flow as well as experimental and theoretical correlations were used to predict the drag forces on the reference object. Flow properties in the flow field above the reference object were calculated and tabulated in detail. These results were compared against numerical results obtained using Computational Fluid Dynamics (CFD) programs. It was concluded that a conical wedge has a higher base drag coefficient than a body with a cylindrical base configuration. For bodies with similar base configurations, a larger conical angle results in a larger pressure foredrag coefficient. Skin friction drag coefficient remains relatively constant as conical angle is varied.